CONCEPTUAL APPROACHES TO INNOVATIVE ACTIVITIES IN RAILWAY TRANSPORT OF UKRAINE - Костенюк, Наталя (SWorldJournal, 2024)
The work considers the development of innovative activity in the field of railway transport in Ukraine as a key element of the modernization of the transport infrastructure and increasing the country's competitiveness on the international transport marke